Tensile failure prediction for cellular lattice structure fabricated by material extrusion using cohesive zone model - Park, Sang-In (2018)
In material extrusion, the geometrical approximation process introduces defects such as voids and gaps in the build plane as well as along the building direction. These serve as crack initiation sites and increase possibility of fracture by crack propagation. As a result, structural members under tensile loading in lattice structures tend to fail at significantly lower stresses than strengths that are estimated only based on elastic or plastic failure criteria. In this paper, we present a failure prediction approach for material extruded cellular lattice structures under tensile loading. The approach is based on a cohesive zone model (CZM) and assesses two failure criteria: elastic failure and fracture. We constructed as-fabricated voxel models for lattice structures and inserted cohesive zone element at interfaces between layers. The failure strength was estimated using the voxel models and are compared with test results.